Environmental monitoring data reveals geographic and depth-based differentiation of benthic fjord communities. (5th May 2022) - Sen, Arunima; Silberberger, Marc J.; Faust, Johan C.; Cochrane, Sabine; Renaud, Paul E.; Reiss, Henning
Abstract: Multi-fjord studies require resources and time usually not afforded to academic projects. We used data from environmental monitoring surveys to conduct an extensive multi-fjord study that allowed us to explore large scale patterns of benthic communities of fjords along the Norwegian coast. We found a distinction between the subarctic Finnmark subprovince and the more temperate West Norwegian subprovince, and within the latter, a distinction between shallow stations (less than 220 m water depth) and deeper stations (greater than 220m water depth). Sedimentary total organic carbon (TOC) content was lower among Finnmark stations compared to West stations at similar water depths and this could account for species that thrive in organic rich sediment being abundant in the latter, as well as the near absence of chemosynthesis-based species from the Finnmark stations. However, neither lower marine primary production due to extensive polar night periods nor less terrigenous carbon input due to sparse tree cover appear to explain the lower TOC of Finnmark stations. In fact, despite the northernmost tree and forest line running through Finnmark, stations in this region had higher C/N rations, which can be indicative of terrigenous carbon input, which could be due to permafrost derived peatlands and marshes that are abundant in this region. We suggest that the observed biogeographic differentiation is not based just on terrestrial or vertical water column carbon fluxes but additionally on sedimentary carbon retention capacity which is linked to grain size. Sediment reworking by species such as capitellid worms could potentially further impact sediment organic matter content. The coarser sediment of Finnmark stations furthermore supports taxa that rely on larger grain sizes. Though few deepwater species were observed, two-thirds of the total taxa enumerated in this study were absent from deep stations (>220 m water depth). Environmental parameters were largely not statistically different between deep stations and shallow stations of either subprovince, but species differences suggest that sediment grain size could explain some of the community differences. This study highlights the value of monitoring data that can be used for gaining understanding over large spatial scales that is not possible through academic budgets and research-funding periods. Highlights: Monitoring data was used to study spatial structure of benthic fjord communities. Differentiation followed region (subarctic vs temperate) and water depth (220 m). Sediment differences in carbon and metal content can explain regional trend. Retention capacity (from percent pelite), not only fluxes basis for regional variation. Percent pelite sole factor that can explain observed depth based differentiation.